2011
DOI: 10.1103/physrevc.84.034303
|View full text |Cite
|
Sign up to set email alerts
|

General treatment of vortical, toroidal, and compression modes

Abstract: The multipole vortical, toroidal, and compression modes are analyzed. Following the vorticity concept of Ravenhall and Wambach, the vortical operator is derived and related in a simple way to the toroidal and compression operators. The strength functions and velocity fields of the modes are analyzed in 208 Pb within the random-phase-approximation using the Skyrme force SLy6. Both convection and magnetization nuclear currents are taken into account. It is shown that the isoscalar (isovector) vortical and toroid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
147
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(160 citation statements)
references
References 58 publications
(181 reference statements)
13
147
0
Order By: Relevance
“…In Ref. [21], they call the former and the latter, the toroidal and vortical modes, respectively, and described general treatment of toroidal, compressive, and vortical modes and their relation to each other. In this paper, we basically follow the descriptions of the TD, CD, and vortical dipole (VD) operators in Ref.…”
Section: Operators and Strengthsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ref. [21], they call the former and the latter, the toroidal and vortical modes, respectively, and described general treatment of toroidal, compressive, and vortical modes and their relation to each other. In this paper, we basically follow the descriptions of the TD, CD, and vortical dipole (VD) operators in Ref.…”
Section: Operators and Strengthsmentioning
confidence: 99%
“…One of the interesting problems is whether the vorticity origin TD mode arises as low-energy resonances in nuclear systems. In works with quasiparticle phonon model (QPM) and random phase approximation (RPA) for such nuclei as 208 Pb and 132 Sn [19,[21][22][23], it has been shown that the TD mode dominates the low-energy part of the ISD strengths whereas the CD mode mainly excites the high-energy part for the ISGDR, indicating that the toroidal property is a key for low-energy dipole resonances. The TD dominant nature of the low-energy E1 resonances has been demonstrated by toroidal flow in transition current densities [1,18,19,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One is the "toroidal mode" originally determined by the second order correction in the long-wave approximation of the transition Eλ operator in an electromagnetic field [10,32], and the other is the "vortical mode" in Ravenhall-Wambach's prescription [11]. Kvasil et al described general treatment of toroidal, compressive, and vortical modes and their relation to each other [15]. They showed that the toroidal mode is a good probe for LE-ISD excitations rather than the vortical mode, though both the TD and vortical dipole (VD) operators can measure the vorticity.…”
Section: Isd Operators and Transition Strengthsmentioning
confidence: 99%
“…The energy of the TD mode is expected to be lower than the ISGDR energy because it conserves the nuclear density. In these years, microscopic calculations with quasiparticle phonon model (QPM) and random phase approximation (RPA) have been achieved, and toroidal natures of the LED excitations in various nuclei have been investigated [3,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%